Hybrid Threats: Essence, Characteristics, Preconditions for Escalation - Kalyuzhna Nataliya H.; Kovtun Taras K. (Problemi Ekonomiki, 2021)
The article aims at clarifying the essence of hybrid threats through systematizing their key characteristics and determining preconditions for conflict escalation. Common definitions of hybrid threats are considered and the lack of a unified approach to their interpretation is emphasized given their diversity and comprehensive nature. The high destructive potential of hybrid threats due to their hidden nature and focus on the most vulnerable aspects of the hybrid aggression object are substantiated. The specifics of carrying out hybrid threats in the economic sphere is analyzed, and the example of foreign trade relations between Ukraine and the Russian Federation shows that the economic sphere serves as a space for hiding and deformalizing a hybrid conflict. The essence of the synergetic effect made by the synchronous realization of hybrid threats in different confrontation areas is considered. It is demonstrated that the key feature of hybrid conflicts is their staying outside the legally justified intervention of other states and international organizations. Emphasis is placed on the rapid spread of hybrid threats in the economic sphere and on the special risks that conflicts hybridization creates for economically weak states. Another important feature of hybrid threats is identified, namely, the high probability of their escalation due to unforeseen events, the global pandemic COVID-19 in particular. It is substantiated that the expected risk of the post-pandemic period is the transition of most national economies to protectionist policies, which will inevitably increase the risk of hybrid threats escalation for economically weak states due to the desire of more powerful states to protect their national economic interests. Having analyzed the specifics of hybrid threats and understanding hybridity as a result of combining different forms, the authors identify the key characteristics of hybrid threats and further combine them into the following groups according to their essence: general aspects; specifics of methods and tools; areas of implementation; prerequisites for efficiency.